Narrative Semiotics in the Epic Tradition The Simile - Nimis, Stephen A. (Indiana University Press, 1988)
In this innovative study, Stephen Nimis applies the insights of semiotics to the analysis of the epic simile in works by Homer, Apollonius of Rhodes, Vergil, Dante, and Milton. Through close structural readings of the similes in these works, Nimis explores the ways texts relate to their narrative traditions and shows how changing cultural contexts produce different ways of conceiving and constructing meaning. He traces these transformations in the epic from the integrated warrior culture of the Iliad to the dissolution of the epic tradition in the cultural world of Milton's Paradise Lost.